Development of a Wordwall-Based Drag and Drop Game for Teaching Arabic Writing Skills - Nafisah, Zakhirotun; Rizal, Hasan Syaiful; Hasyim, Mochamad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to develop and evaluate the effectiveness of a Wordwall-based drag-and-drop learning medium in improving students’ (Arabic Writing Skills). The research employed a Research and Development (R&D) approach using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, interviews, questionnaires, pretests, and posttests. This study involved the entire student population of MTs Al-Hikmaturrohmaniyah for the 2024/2025 academic year, with the sample selected using cluster sampling, focusing on 7th-grade students as a representative cluster of the overall population. Quantitative data were collected through pretests and posttests to measure improvements in Arabic Writing Skills and analyzed using descriptive statistics and the Paired Sample t-test. Qualitative data from observations, interviews, and questionnaires were analyzed using Miles and Huberman’s model, focusing on evaluating the effectiveness of Wordwall-based media from both teacher and student perspectives. Wordwall media significantly improved students' Arabic Writing Skills, increasing those meeting the KKM from 7 to 18. Statistical analysis confirmed a significant difference between pretest and posttest scores, indicating the media’s effectiveness in enhancing learning outcomes and student motivation.